Physiological Responses of Winged Bean [Psophocarpus Tetragonolobus (L.) Dc.] to Support Systems and Ratooning - Rahman, Md. Motior (1998)
Winged bean is an indeterminate, climbing, perennial legume that needs support to achieve high yields. The major constraint to large scale production of winged bean is the need for trellising which incurred an additional cost of production. After harvesting of young or mature pods plants can be cut and the pollarded root stock produces a ratoon crop. Ratooning, a new technique for seed production of winged bean, can reduce the initial expenditure on support structures. Therefore, these studies on the effects of support systems and ratooning on growth and seed production of winged bean were conducted under humid tropical field conditions to document some experimental evidence. Results from the first experiment revealed that when compared to unsupported control, support height of 1 and 2 m caused a significant increase in leaf area index (LAI), net photosynthesis, relative growth rate (RGR), nodule activity, solar radiation interception (SRI), pattern of dry matter accumulation and partitioning and consequently the seed yield of winged bean. Plants grown on a support height of2 m had enhanced leaf growth, pod number and total dry matter yield when compared to those on support height of Im and unsupported plants. In the subsequent experiment, the root stock of the main crop was cut off at 126, 140, 154 and 168 days after germination (DAG) and the ratooned crops maintained for the next two crop cycles (126 days/crop cycle). The results suggested that ratooning of winged bean at 126 or 140 DAG would lower the investment expenditure on support structures and produced the highest cumulative seed yield per unit area per unit time.